Polymer composition for polymer solid electrolyte and polymer solid electrolyte membrane for all-solid-state secondary battery comprising the same

KR103012812B1Active Publication Date: 2026-09-01LOTTE CHEM CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020230171595
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2026-09-01
Estimated Expiration
2043-11-30

Smart Images

  • Figure 112023134495375-PAT00004_ABST
    Figure 112023134495375-PAT00004_ABST
Patent Text Reader

Abstract

The present invention relates to a resin composition for a polymer solid electrolyte comprising a lithium salt; and a blended polymer of a PAN (polyacrilonitrile) polymer and a PAN-co-PMMA (poly(acrylonitrile-co-methyl methacrylate)) copolymer, and a polymer solid electrolyte membrane for an all-solid-state secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a resin composition for a polymer solid electrolyte and a polymer solid electrolyte membrane for an all-solid-state secondary battery comprising the same. Background Technology

[0002] All-solid-state rechargeable batteries, which are attracting attention as next-generation batteries, demonstrate the potential for high-output and high-stability batteries by solidifying the material that allows lithium ions to move between the cathode and anode instead of using the separator and liquid electrolyte previously used in LiBs, thereby reducing the risk of lithium dendrites and preventing adverse reactions with liquid electrolytes. The solid electrolyte materials mainly being developed for all-solid-state rechargeable batteries include sulfide-based, oxide-based, and polymer-based types. Sulfide-based solid electrolytes have the disadvantage of high interfacial resistance, requiring compression at high temperatures and pressures, and being vulnerable to moisture. Additionally, oxide-based solid electrolytes have the disadvantage of relatively low ionic conductivity. In contrast, polymer-based solid electrolytes are easy to manufacture and operate under room temperature conditions, leading to extensive research being conducted on them. Prior art literature

[0003] Republic of Korea Published Patent Application No. 10-2022-0026768 The problem to be solved

[0004] The present invention aims to provide a resin composition for a polymer solid electrolyte that has high stability and can improve the capacity retention rate during charging and discharging, and a polymer solid electrolyte membrane for an all-solid-state secondary battery containing the same. means of solving the problem

[0005] One embodiment of the present invention provides a resin composition for a polymer solid electrolyte comprising: a lithium salt; and a blended polymer of a PAN (polyacrilonitrile) polymer and a PAN-co-PMMA (poly(acrylonitrile-co-methyl methacrylate)) copolymer.

[0006] Another embodiment of the present invention provides a polymer solid electrolyte membrane for an all-solid-state secondary battery comprising the polymer solid electrolyte resin composition.

[0007] Another embodiment of the present invention provides an all-solid-state secondary battery comprising the polymer solid electrolyte membrane for the all-solid-state secondary battery. Effects of the invention

[0008] A polymer solid electrolyte membrane for an all-solid-state secondary battery comprising a resin composition for a polymer solid electrolyte according to the present invention has high lithium ion conductivity and enables the even deposition of lithium ions during charging and discharging, thereby improving battery stability and lifespan. Brief explanation of the drawing

[0009] FIG. 1 is a schematic diagram showing the mixing of a PAN polymer and a PAN-co-PMMA copolymer of a blending polymer according to the present invention. FIG. 2 shows the surface of a lithium metal anode after evaluating the discharge retention rate of a coin cell according to Comparative Example 1. FIG. 3 shows the surface of a lithium metal anode after evaluating the discharge retention rate of a coin cell according to Example 1. FIG. 4 shows the results of evaluating the discharge capacity retention rate of a coin cell according to Examples 1 to 3 and Comparative Example 1. Specific details for implementing the invention

[0010] In this specification, when a part is described as "comprising" a certain component, it means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0011] In this specification, when a member is described as being located "on" another member, this includes not only cases where a member is in contact with another member, but also cases where another member exists between the two members.

[0012] In this specification, the unit "parts by weight" may refer to the ratio of weight between each component.

[0013] In the case of PAN (polyacrilonitrile) polymers, which have been suggested as potential for use as conventional polymer-based solid electrolytes, their ionic conductivity is low, so improvement is required. To address this problem, the inventors continued research on solid polymer electrolyte membranes based on PAN polymers, and as a result, completed the following invention.

[0014] The present invention will be described in detail below.

[0015] One embodiment of the present invention provides a resin composition for a polymer solid electrolyte comprising: a lithium salt; and a blended polymer of a PAN (polyacrilonitrile) polymer and a PAN-co-PMMA (poly(acrylonitrile-co-methyl methacrylate)) copolymer.

[0016] In the case of polyacrilonitrile (PAN) polymers, there was a problem with insufficient performance for application as polymer solid electrolyte membranes due to their low ionic conductivity. Accordingly, a method was investigated to facilitate the movement of lithium ions by forming amorphous regions within the PAN polymer structure. However, in the case of blended polymers formed by mixing PAN polymers and PMMA polymers, they did not mix and existed as separate phases, resulting in poor lithium ion movement and making it impossible to apply them as polymer solid electrolyte membranes due to excessively high surface non-uniformity when manufactured. In contrast, it was discovered that when blending PAN polymers with PAN-co-PMMA (poly(acrylonitrile-co-methyl methacrylate)) copolymers as in the present invention, the PAN monomers and PAN polymers within the PAN-co-PMMA copolymer can be mixed with each other, thereby minimizing the problem of insolubility between heterogeneous polymers.

[0017] FIG. 1 is a schematic diagram showing the mixing of a PAN polymer and a PAN-co-PMMA copolymer of a blending polymer according to the present invention. Specifically, in the blending polymer of the present invention, the PAN polymer can be inserted into the crystalline chain section of the PAN-co-PMMA copolymer and mixed, and the amorphous chain section of the PAN-co-PMMA copolymer acts as a nanochannel for the movement of lithium ions, thereby facilitating the movement of lithium ions. Specifically, since the PMMA monomer of the PAN-co-PMMA copolymer has an acrylic functional group that activates the dissociation of lithium salts, the movement of lithium ions is smooth, and due to its elastic properties, it can also have a dendrite blocking effect. Furthermore, since the blending polymer according to the present invention has high miscibility, it is possible to manufacture a smooth membrane by minimizing surface irregularities when forming a polymer solid electrolyte membrane.

[0018] According to one embodiment of the present invention, the weight ratio of the PAN polymer and the PAN-co-PMMA copolymer in the blending polymer may be 6:4 to 9.5:0.5. Specifically, the weight ratio of the PAN polymer and the PAN-co-PMMA copolymer in the blending polymer may be 6.5:3.5 to 9.5:0.5, 7:3 to 9.5:0.5, 7.5:2.5 to 9.5:0.5, 8:2 to 9.5:0.5, 8.5:1.5 to 9.5:0.5, 8.7:1.3 to 9.3:0.7, 8.8:1.2 to 9.2:0.8, or about 9:1. Within the weight ratio range of the above PAN polymer and PAN-co-PMMA copolymer, the lithium ion conductivity of the polymer solid electrolyte membrane is excellent, and the reduction in capacity retention rate due to charging and discharging can be minimized.

[0019] According to one embodiment of the present invention, the weight-average molecular weight of the PAN-co-PMMA copolymer may be 5,000 g / mol or more and 250,000 g / mol or less. If the weight-average molecular weight of the PAN-co-PMMA copolymer is less than the above range, the polymer solid electrolyte membrane may have excessively elastic properties and may not be able to perform its function as a polymer solid electrolyte membrane. In addition, if the weight-average molecular weight of the PAN-co-PMMA copolymer exceeds the above range, it may not dissolve in a solvent or the viscosity may increase excessively, causing problems that make film casting difficult.

[0020] According to one embodiment of the present invention, the weight-average molecular weight of the PAN polymer may be 100,000 g / mol or more and 200,000 g / mol or less. If the weight-average molecular weight of the PAN polymer is below the above range, a decrease in mechanical properties of the electrolyte membrane, such as tensile strength, may occur, and if it exceeds the above range, a problem may arise in which ion conductivity decreases due to crystallinity. Therefore, when the weight-average molecular weight of the PAN polymer is within the above range, the mechanical properties and ion conductivity required for a polymer solid electrolyte membrane can be satisfied.

[0021] According to one embodiment of the present invention, the lithium salt may be selected from LiFSI (Lithium bis(fluorosulfonyl) imide), LiTFSI (lithium bis(trifluoromethane sulfonyl) imide), LiPF6, LiBF4, LiAsF6, LiClO4, LiCsPF6, LiNO3, LiPO2F2, LiBr, LiBOB (lithium bis(oxalato) borate), LiDFOB (lithium difluoro(oxalate) borate), LiCF3SO3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO3CF3)2, LiC4F9SO3, LiAlCl4, and LiTfl (lithium trifluoromethanesulfonate). The lithium salt may serve to facilitate the movement of lithium ions within a polymer solid electrolyte membrane. Furthermore, Li, which is a cation of the lithium salt within the polymer solid electrolyte membrane + While the movement of lithium ions is facilitated, the movement of anions is restricted within the polymer solid electrolyte membrane, allowing lithium ions to be evenly deposited on the negative electrode during charging and discharging of the battery, thereby suppressing the formation of lithium dendrites. To maximize this effect, according to one embodiment of the present invention, the content of the lithium salt may be 30 parts by weight or more and 70 parts by weight or less per 100 parts by weight of the blending polymer. If the content of the lithium salt is below the above range, sufficient lithium ion conductivity may not be achieved, and if it exceeds the above range, it may not dissolve sufficiently in the solution, which may cause problems in manufacturing a uniform membrane.

[0022] According to one embodiment of the present invention, the resin composition for a polymer solid electrolyte may further include a plasticizer. The plasticizer may enable smoother movement of ions within the coating layer.

[0023] According to one embodiment of the present invention, the plasticizer may include at least one selected from the group consisting of gamma-butyrolactone (GBL), glutaronitrile (GN), and succinonitrile (SN). Specifically, the plasticizer may be glutaronitrile (GN).

[0024] According to one embodiment of the present invention, the resin composition for a polymer solid electrolyte may further include a solvent. Specifically, according to one embodiment of the present invention, the solvent may be an organic solvent. More specifically, the organic solvent may comprise at least one selected from the group consisting of N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyl lactone, 1,2-dimethoxyethane, tetrahydroxyfuran, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivative, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivative, tetrahydrofuran derivative, ether, methyl propionate, and ethyl propionate.

[0025] Another embodiment of the present invention provides a polymer solid electrolyte membrane for an all-solid-state secondary battery comprising the polymer solid electrolyte resin composition. The polymer solid electrolyte membrane for an all-solid-state secondary battery may comprise a cured product of the polymer solid electrolyte resin composition, and specifically, may be a cured product of the polymer solid electrolyte resin composition.

[0026] Another embodiment of the present invention provides a method for manufacturing a polymer solid electrolyte membrane for an all-solid-state secondary battery using the polymer solid electrolyte resin composition described above. Specifically, the method comprises the steps of: preparing a polymer solid electrolyte resin composition in which a lithium salt and a blended polymer of a PAN (polyacrilonitrile) polymer and a PAN-co-PMMA (poly(acrylonitrile-co-methyl methacrylate)) copolymer are dissolved in a solvent; and forming a polymer solid electrolyte membrane using a wet coating method with the polymer solid electrolyte resin composition. At this time, the polymer solid electrolyte resin composition comprises the composition and contents as described above.

[0027] According to one embodiment of the present invention, the wet coating method may involve applying the polymer solid electrolyte resin composition by a bar coating, doctor blade coating, spray coating, flow coating, roll coating, spin coating, or gravure coating method, and then drying it.

[0028] According to one embodiment of the present invention, the coating thickness of the resin composition for a polymer solid electrolyte in the wet coating method may be 10 μm to 50 μm, 15 μm to 40 μm, or 20 μm to 35 μm. Within the above thickness range, surface irregularities of the polymer solid electrolyte film after drying can be minimized and necessary rigidity can be secured. By setting the coating thickness as above, the surface of the coating layer may rise and the thickness may increase due to the surface tension of the resin composition for a polymer solid electrolyte after coating, and the thickness of the polymer solid electrolyte film after final drying may be 50 μm to 150 μm or 80 μm to 100 μm.

[0029] Another embodiment of the present invention provides an all-solid-state secondary battery comprising the polymer solid electrolyte membrane for the all-solid-state secondary battery. The all-solid-state secondary battery comprises a positive electrode and a negative electrode provided via the aforementioned polymer solid electrolyte membrane. The all-solid-state secondary battery may be a lithium metal all-solid-state secondary battery in which the polymer solid electrolyte membrane is applied and lithium metal is applied to the negative electrode. However, it is not limited thereto, and the positive electrode, the negative electrode, and the components of the all-solid-state secondary battery may be applied as they are known in the art for the intended purpose.

[0030] Hereinafter, the present invention will be described in detail with reference to examples to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention is not to be interpreted as being limited to the embodiments described below. The embodiments of this specification are provided to more completely explain the present invention to those with average knowledge in the art.

[0031] [Examples and Comparative Examples]

[0032] A resin composition for a polymer solid electrolyte was prepared with the composition shown in Table 1 below. Specifically, ethylene carbonate was prepared as a solvent for dissolving the polymer, and glutaronitrile (GN), a plasticizer, was added thereto. Then, a PAN polymer (Aldrich, Mw: 150,000 g / mol) and a PAN-co-PMMA copolymer (Aldrich, PAN 94 wt% and PMMA 6 wt%, Mw: 200,000 g / mol) were dissolved in the prepared solvent, and then a lithium salt (LiPF6) was added and dissolved to prepare a resin composition for a polymer solid electrolyte.

[0033] PAN / PAN-co-PMMA (weight ratio) PAN (weight ratio) PAN-co-PMMA (weight ratio) Solvent (weight ratio) Lithium salt (by weight) Comparative Example 1 10 10 0 85 5 Example 1 9 / 1 9 1 85 5 Example 2 8 / 2 8 2 85 5 Example 3 7 / 3 7 3 85 5

[0034] The prepared polymer solid electrolyte resin composition was cast onto a glass substrate using a doctor blade to a set thickness of 10 μm. Then, the polymer solid electrolyte membrane was obtained by drying in a vacuum oven at about 70°C for about 1 hour.

[0035] Then, a CR2032 coin cell (diameter 20 mm, thickness 32 mm) was fabricated, and its ion conductivity and discharge capacity retention rate were evaluated. NCM811 was used as the anode and Li metal foil as the cathode, and a fabricated polymer solid electrolyte membrane was provided between the anode and the cathode. The results of evaluating the ion conductivity of the fabricated coin cell and the discharge capacity retention rate at a rate of 0.3 C charge / discharge are shown in Table 2 below.

[0036] PAN / copolymer weight ratio Ionic conductivity Discharge capacity retention rate Comparative Example 1 10 / 0 1.1 80%@80cycle Example 1 9 / 1 1.8 94%@100cycle Example 2 8 / 2 1.5 88%@80cycle Example 3 7 / 3 1.6 86%@80cycle

[0037] Figure 2 shows the surface of a lithium metal anode after evaluating the discharge retention rate of a coin cell according to Comparative Example 1. Figure 3 shows the surface of a lithium metal anode after evaluating the discharge retention rate of a coin cell according to Example 1. Referring to Figures 2 and 3, it can be confirmed that the polymer solid electrolyte according to Example 1 allows for the even deposition of lithium ions onto the anode during charging and discharging due to its high lithium ion conductivity. It can be estimated that such even lithium deposition contributes to improving the battery life by suppressing the formation of lithium dendrites.

[0038] Figure 4 shows the results of evaluating the discharge capacity retention rate of coin cells according to Examples 1 to 3 and Comparative Example 1. Specifically, Examples 1 to 3, in which a blend of PAN polymer and PAN-co-PMMA copolymer was applied to a polymer solid electrolyte membrane, exhibited improved ion conductivity and battery life characteristics compared to Comparative Example 1, in which only PAN polymer was applied to the polymer solid electrolyte membrane. This implies that the movement of lithium ions is freer through the PAN polymer and the PAN-co-PMMA copolymer PMMA. Among the examples, Example 1, in which the weight ratio of PAN polymer to PAN-co-PMMA copolymer was 9:1, exhibited the best battery characteristics. This is the result of the most smooth movement of lithium ions occurring as the content of the PAN polymer and PAN-co-PMMA copolymer was optimized during blending.

Claims

Claim 1 A polymer solid electrolyte membrane for an all-solid-state secondary battery, comprising a lithium salt; and a blending polymer of a PAN (polyacrilonitrile) polymer and a PAN-co-PMMA (poly(acrylonitrile-co-methyl methacrylate)) copolymer, wherein the weight ratio of the PAN polymer to the PAN-co-PMMA copolymer in the blending polymer is 6.5:3.5 to 9.5:0.

5. Claim 2 delete Claim 3 A polymer solid electrolyte membrane for an all-solid-state secondary battery according to claim 1, wherein the weight-average molecular weight of the PAN-co-PMMA copolymer is 5,000 g / mol or more and 250,000 g / mol or less. Claim 4 A polymer solid electrolyte membrane for an all-solid-state secondary battery, wherein, in claim 1, the weight-average molecular weight of the PAN polymer is 100,000 g / mol or more and 200,000 g / mol or less. Claim 5 A polymer solid electrolyte membrane for an all-solid-state secondary battery according to claim 1, wherein the content of the lithium salt is 30 parts by weight or more and 70 parts by weight or less per 100 parts by weight of the blending polymer. Claim 6 delete

Citation Information

Patent Citations

  • Polymer electro composition containing acrylonitle and alkylmetacryllate copolymer

    KR1019990012185A

  • Solid electrolyte, lithium battery comprising solid electrolyte

    KR1020170092327A

  • Method for manufacturing multicomponent system solid high molecule electrolyte and lithium high molecule battery thereof

    KR1020000003092A